Philippus und der äthiopische Kämmerer (apg 8,26-40): Von der Bibel lernen, Lehrer zu sein - Gradl, Hans-Georg (Trierer theologische Zeitschrift, 2017)
Teaching relision in school today is a challenging task. The story of Philip and the Ethiopian eunuch (Acts 8:26-40) speaks about the self-understanding and the hmc tion of a Christian teacher and inspires the readers. Philip asks only one single question and does not give a long and complicated monologue. He stands at the side and accom panies the man on his route and does not stop the chariot. Philip takes a desert road to meet the Ethiopian official and becomes part of his life. By looking back on this story the reader should consider the purpose and manner of his personal teaching and proclamation.